Estimating the Relationship between Industrial Production and Economic Growth for the Period (1980-2020), an Applied Study in the Iraqi Economy According to Kaldor’s Law - Muhammad Najeeb, Shaima; Jasim Arab, Hafidh (Academic Journal of Nawroz University, 2023)
In this research, we will discuss and test (Kaldor’s laws of growth) in the case of studying industrial output in Iraq and economic growth, as the first law states that (industry is an engine of economic growth) for two reasons: the dominance of returns to scale, and the growth of industrial output is considered a net increase for the economy as a whole. Especially under the assumption that economies are dual, while the second law, which is called Verdon's Law, states (there is a long-term positive causal relationship between industrial output and economic growth), and using data from international publications for the period (- 1980 - 2020), the theoretical and empirical differences related to By estimating and interpreting Kaldor's laws of growth, we present and discuss some evidence.